Narrative im Bruch: theoretische Positionen und Anwendungen - Babka, Anna; Bidwell-Steiner, Marlen; Müller-Funk, Wolfgang (Broken narratives, 2016)
This book centers on narrative rupture, seeking to elucidate its role as a primary epistemological tool. Rupture can be conceived of as a ‘travelling concept’ (Bal 2002), as a basic cognitive instrument. On account of its elementary structure and rich semiotic implications, it has traversed academic time and space, serving ever more as an integral part of a wide variety of artistic, intellectual and ideological paradigms. This first volume of a series dealing with the relationship between narration and rupture approaches the concept of narrative disruption on a meta-methodological level. By laying the foundations for a general cultural theory of narrative rupture, we hope to contribute to the larger project of a narratology-based theory of culture.; Aus genuin transdisziplinärer Perspektive entfaltet und diskutiert der Band insbesondere theoretische Fragestellungen, die sich aus der Beziehung von Narration und Bruch ergeben. Dabei kommen nicht nur vielfältige narratologische Modelle zu Wort, vielmehr wird das Thema der gebrochenen und brüchigen Narrative auch im Hinblick auf theoretische Basiskonzepte vielstimmig erörtert und breit konturiert. Das Spektrum der Beiträge reicht von gleichsam ›neo‹-narratologischen zu kognitionstheoretischen, von philosophisch dekonstruktiven zu gender- und queertheoretischen bis hin zu biographie- und autobiographietheoretischen Ansätzen.
Keywords: Aufsatzsammlung; Erzähltheorie